Pandemic-induced increases in container freight rates: Assessing their domestic effects in a globalized world - José Pulido (Graduate Institute of International and Development Studies, 2022)
The Covid-19 pandemic disrupted the international transportation industry, causing container freight rates to reach record highs from late 2020 and into 2021. I evaluate the dynamic effects of the observed increases in container freight rates all around the world on the domestic inflation, real consumption, and the allocation of labor of a particular country (Colombia). For this, I use a quantitative model of international trade with out-of-steady-state transitional dynamics, input and output linkages and frictions in the labor markets. The framework allows for a quantification not only of the direct impact of the freights for the goods shipped in and out of Colombia, but also of the indirect impact of the increases in freights in the rest of the world. To identify the transportation costs shocks in the model, I estimate trade elasticities to freight rates, using an IV estimator that takes advantage of the heterogeneous timing of the lockdowns. Results indicate that worldwide increases in container freight rates caused a sizable impact on Colombian domestic inflation (2.4% on average), a welfare loss of 1.4%, and moderate effects on labor reallocations.
Keywords: F16; F62; F17; 330; International trade; container freights; Covid-19 pandemic; welfare effects; general equilibrium